Role of the immune component of tumor microenvironment in the efficiency of cancer treatment: perspectives for the personalized therapy - Stakheyeva, Marina; Kzhyshkowska, Julia (Current pharmaceutical design, 2017)
Despite significant progress in cancer diagnostics and development of novel therapeutic regimens, successful treatment of advanced forms of cancer is still a challenge and may require personalized therapeutic approaches. In this review, we analyzed major mechanisms responsible for tumor cells chemoresistance and emphasized that intratumor heterogeneity is a critical factor that limits efficiency of cancer treatment. Intratumor heterogeneity is caused by genomic instability in cancer cells, resulting in the selection of resistant clones. Moreover, cancer cells in solid tumors are surrounded by cellular and molecular microenvironment that actively influences tumor cell behavior. Local tumor microenvironment (TME) consisting of immune cells with diverse phenotypes and functions strongly contributes to intratumor heterogeneity and modulates responses to treatment. Thus, targeting specific components of TME is a novel treatment strategy that can improve the outcome of conventional anti-cancer therapy. Here, we discuss modern immunotherapeutic approaches based on targeting tumorinfiltrating immune cells including neutrophils, dendritic cells, NK cells, T cells, B cells and macrophages. Among those, tumor-associated macrophages (TAM) that display a pronounced heterogeneity and phenotypic plasticity appear to be a major component in the TME of solid tumors, and emerge as perspective targets for cancer immunotherapy. TAM intratumor heterogeneity and the possible existence of patient-specific phenotype signature generate the basis for the development of individualized TAM-based therapeutic approaches.